Study of silvopastoral systems as an alternative for the sustainable management of livestock - Arciniegas-Torres, Sandra Patricia; Flórez-Delgado, Dixon Fabián (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Silvopastoral systems are seen as a feasible solution for livestock with a focus on sustainability, particularly because they contribute to food security, by generating food products, jobs and income. However, livestock has also generated negative impacts on the environment, such as soil compaction, detriment of biodiversity, deforestation, pollution of water sources and emission of greenhouse gases, which contribute to climate change, this being one of the most worrisome environmental problems, since it harms all living beings on the planet. For this reason, it is essential to delve into the issue of silvopastoral systems, their types, advantages and disadvantages to present them as an alternative solution that contributes to mitigate the livestock effect on the environment, representing a viable option for its conservation and adaptation to climate change; this is achieved by allowing the intensification of livestock production through the optimization and rational use of natural resources.